Kepemimpinan Kepala Sekolah dalam Mengembangkan Budaya Religi Di SMP Islam Jabal Hikmah Suwang - Irwan Yon Hadi; Samsul Hadi; Asma Lely Muti Suklan (Pendidikan Al-Gafari, 2023)
Head school as a leader is accepted metaphor general, with the teacher as follower or teacher as worker. Later This increasing Lots educational reform literature that is consistently emphasizes that effective leaders do not apply in a way straight away. By general study aims to know how leaders head schools in developing culture and religion at Jabal Hikmah Suwangi Islamic Middle School. Study this nature of qualitative descriptive. Data collection techniques use method observation, interviews, and documentation. The research purpose is to know the leadership head school and, the culture of religion at the school as the impact of the development culture of religion at Jabal Hikmah Suwangi Islamic Middle School findings study This is: Leadership at Jabal Hikmah Suwangi Islamic Middle School is supportive/democratic leadership that is oriented towards vision and mission, decides with method discussion as well as take policies that don't harm party anywhere. Culture religion applied at Jabal Hikmah Suwangi Islamic Middle School is uniform Islamic schools: 1) boys wear a shirt green, black pants, and a skullcap (piece) and 2) Women wear clothes brackets colored green, skirt black, and green hijab with the Jabal Hikmah logo on it. Next 3). Required culture Salat Dhuha congregation and continue with deep Language Arab before entering class, 4) Culture greetings and greetings, 5) Culture Embarrassment come late, 6) Culture discipline as well as culture Salat noon congregation before going home school, and so on. In an attempt to develop a culture of religion things to do is give motivation to all school stakeholders to continue Work The same in developing a culture of religion in school to become a school that can inspire schools other.